Numerical heat transfer and fluid flow - Patankar Suhas V (London Taylor & Francis, 2004)
This book is concerned with heat and mass transfer, fluid flow, chemical reaction, & other related processes that occur in engineering equipment in the natural environment and in living organisms. The 1st three chapters constitute the preparatory phase.
Keywords: Fluid dynamics; Heat transmission; Numerical analysis